Korelasi Antara Ekstrakurikuler Pramuka dengan Perkembangan Sosial Siswa di Madrasah Ibtidaiyah - Khotimah, Khusnul; Ratnasari, Khurin’in (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
The purpose of this study was to determine the correlation between extracurricular scouting and students' social development. The number of respondents in this study were 30 students of MI Ma'arif NU Nurul Islam Yosowilangun Kidul and used quantitative correlation methods. Based on the results of the study, it is concluded that there is a correlation between extracurricular scouting and students' social development. This can be seen from the results of hypothesis testing between the scout extracurricular variable (X) and the student social development variable (Y) which shows 0.796 (r count) greater than 0.334 (r table), namely 0.796> 0.334. The significance value is less than 0.05, namely 0.000 <0.05, which means Ha is accepted and Ho is rejected. This means that the increase in extracurricular scout participation will also increase the social development of students at MI Ma'arif NU Nurul Islam Yosowilangun Kidul.